Increased calcineurin expression after pilocarpine-induced status epilepticus is associated with brain focal edema and astrogliosis. (2nd June 2016) - Liu, Jinzhi; Li, Xiaolin; Chen, Liguang; Xue, Ping; Yang, Qianqian; Wang, Aihua
Abstract : Calcineurin plays an important role in the development of neuronal excitability, modulation of receptor's function and induction of apoptosis in neurons. It has been established in kindling models that status epilepticus induces brain focal edema and astrocyte activation. However, the role of calcineurin in brain focal edema and astrocyte activation in status epilepticus has not been fully understood. In this study, we employed a model of lithium-pilocarpine-induced status epilepticus and detected calcineurin expression in hippocampus by immunoblotting, brain focal edema by non-invasive magnetic resonance imaging (MRI-7T) and astrocyte expression by immunohistochemistry. We found that the brain focal edema was seen at 24 h after status epilepticus, and astrocyte expression was obviously seen at 7 d after status epilepticus. Meanwhile, calcineurin expression was seen at24 h and retained to 7 d after status epilepticus. A FK506, a calcineurin inhibitor, remarkably suppressed the status epilepticus-induced brain focal edema and astrocyte expression. Our data suggested that calcineurin overexpression plays a very important role in brain focal edema and astrocyte expression. Therefore, calcineurin may be a novel candidate for brain focal edema occurring and intracellular trigger of astrogliosis in status epilepticus.